Metabolomic analysis reveals astaxanthin biosynthesis in heterotrophic microalga Chromochloris zofingiensis. (April 2023) - Chen, Qiaohong; Chen, Yi; Hu, Qiang; Han, Danxiang
Graphical abstract: Highlights: The regulatory mechanism of induction stages on astaxanthin synthesis was studied. The glycolysis, PPP, and TCA cycle were enhanced under the induction conditions. The enhancement of fatty acids promoted the process of esterification. Gly and GABA promoted both cell growth and astaxanthin accumulation. The highest astaxanthin yield was 1.97-fold higher than that of the control. Abstract: The utilization of gibberellic acid-3, high carbon/nitrogen ratio and salinity concentration can effectively enhance astaxanthin biosynthesis in Chromochloris zofingiensis under the heterotrophic conditions, but the underlying mechanisms remained yet to be investigated. The metabolomics analysis revealed that enhancement of the glycolysis, pentose phosphate pathways (PPP), and tricarboxylic acid (TCA) cycle led to astaxanthin accumulation under the induction conditions. The increased fatty acids can significantly increase astaxanthin esterification. The addition of appropriate concentrations of glycine (Gly) and γ-aminobutyric acid (GABA) promoted astaxanthin biosynthesis in C. zofingiensis, as well as benefiting for biomass yield. With the addition of 0.5 mM GABA, the astaxanthin yield increased to 0.35 g·L −1, which was 1.97-fold higher than that of the control. This study advanced understanding about astaxanthin biosynthesis in heterotrophic microalga, and provided novel strategies for enhanced astaxanthin production in C. zofingiensis .